Social context of disclosing HIV test results: HIV testing in Tanzania - Lugalla, Joe L.P.; Yoder, P. Stanley; Madihi, Charles Mlwande; Sigalla, Huruma L.; Mrutu, Nipael E. (DHS Qualitative Research Studies No. 15, 2008)
This study examined the circumstances and social contexts in which individuals in Tanzania were tested and counseled for HIV, and patterns in disclosure of test results to partners, family, and friends. The research sought to discover how people experienced these processes based on their own descriptions. The overall objectives of this study were to understand people’s experiences in showing their own HIV test results to others, to discover the pattern of disclosure among individuals tested (whether or not disclosure occurred, to whom, how it was done, after how long), and to discern the role of social relations in facilitating disclosure to others. A better understanding of factors that facilitate disclosure can be useful to programmes that promote disclosure of HIV test results.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents the findings from a qualitative research study conducted by the Centre for Strategic Research and Development in Dar es Salaam, with technical assistance from Macro International Inc. This publication was made possible through support provided by the United States Agency for International Development (USAID) under the terms of Award No. GPO-C-00-03-00002-00 and the President’s Emergency Plan for AIDS Relief (PEPFAR). The opinions expressed in this report are those of the authors and do not necessarily reflect the views of the Government of Tanzania, the United States Government, or USAID. MEASURE DHS assists countries worldwide in the collection and use of data to monitor and evaluate population, health, and nutrition programs. Additional information about the MEASURE DHS project can be obtained by contacting Macro International Inc., Demographic and Health Research Division, 11785 Beltsville Drive, Suite 300, Calverton, MD 20705 (telephone: 301-572-0200; fax: 301- 572-0999; email: reports@macrointernational.com; internet: www.measuredhs.com).